Potential of Islamic Cemetery Complexes in Barus-North Sumatra as Archaeological Tourism Destinations - Maler, Wani (Andalas International Journal of Socio-Humanities, 2024)
Historical and Archaeological Potential Exploration Program in Barus, Central Tapanuli Regency, North Sumatra that was carried out in 2017 had discovered Islamic cemetery complexes distributed throughout the area that have potential as destinations for archaeological tourism. This is supported by the data obtained from field surveys to each cemetery complex and focus group discussion conducted with local residents of Barus. This study focuses on exploring the potential of five cemetery complexes comprising the Mahligai Cemetery, Papan Tinggi Cemetery, Tuan Ambar Cemetery, Ibrahim Syah Cemetery and Tuan Machdum Cemetery to serve as archaeological tourism destinations. The process of spreading Islam carried out by the ulama or Muslim scholars and the existence of various types of tombstones are subjects of attraction for visitors. In the process of developing a cemetery complex as a destination, it is necessary to improve public facilities such as the construction of museums or galleries, places of worship, parking lots, and public toilets. Improving the human resources are also a necessity, which can be done by empowering the local residents.